Correlates of relative lethality and suicidal intent among deliberate self-harm patients. - Haw, C; Hawton, K; Houston, K; Townsend, E (2003)
Conflicting findings have been reported regarding the relationship between the potential lethality of acts of deliberate self-harm (DSH) and suicidal intent, and how each relates to patient characteristics. This study examines the relationship of suicidal intent of DSH to lethality, the relationship of both to patient characteristics, and determines if intent or lethality are risk factors for repetition of DSH. Potential lethality and Suicide Intent Scale (SIS) scores for DSH episodes were examined in a representative sample of 150 patients presenting to a general hospital. Follow-up interviews were completed 12 to 20 months later. Lethality was strongly associated with high intent. Both lethality and intent were associated with male gender. Suicidal intent but not lethality was associated with the presence of psychiatric disorder and depression. Intent was significantly correlated with hopelessness scale score. Although intent was correlated with both depression and self-esteem scale scores, these correlations became nonsignificant when the effect of hopelessness was removed. Repetition of DSH during the follow-up period was related to neither lethality nor intent scores for the original episodes. Lethality and suicidal intent, although related, have somewhat different correlates. Both should be considered when assessing DSH patients, but their relationship to further suicidal behavior does not appear to be straightforward.